Gangguan pola bangun-tidur setelah cedera kepala - Moses Kharisma Setyawan; Sri Maliawan; Tjokorda Gde Bagus Mahadewa; I Wayan Niryana; Dewa Putu Wisnu Wardhana (Intisari Sains Medis, 2021)
Traumatic brain injury is a common trauma. Traumatic brain injury is commonly followed by sleep disorder such as insomnia, hypersomnia and circadian rhythm disturbance. Sleep disorder can cause many complications, including the worsening of the brain injury prognosis. Insomnia occurs in 29% traumatic brain injury patient. Insomnia suspected due injury in inferior frontal, anterior temporal including basal forebrain, also sympathetic nerve hyperactivity. Insomnia increase the risk of stroke, disability and mood disturbance. Hypersomnia occurs in 28% traumatic brain injury patients. Hypersomnia suspected due orexin decrease and injury in sleep promoting area. Hypersomnia suspected related to recovery, less activity time and accident due sleepiness. There are no prevalence data of circadian rhythm disturbance after traumatic brain injury. This disturbance is caused by injury in supra-chiasmatic nucleus and related to global worsening on the patient. Insomnia and circadian rhythm disturbance are highly linked with injury area, but hypersomnia is not particularly linked to any area and only related to orexin decrease. Insomnia and circadian rhythm disturbance are highly related to the worsening condition on the patient, but hypersomnia is associated with recovery and not particularly related to any disturbances. It is hoped that understanding the sleep disorder after traumatic brain injury can rise the alertness of this matter and encourage clinicians to increase the quality of sleep disorder due to traumatic brain injury management.   Cedera kepala merupakan salah satu cedera yang umum terjadi. Cedera ini sering diikuti dengan gangguan tidur seperti insomnia, hipersomnia dan gangguan ritme sirkadian. Gangguan ini sering dapat menyebabkan berbagai komplikasi termasuk memperparah penyembuhan cedera kepala. Insomnia setelah cedera kepala terjadi sebanyak 29%. Insomnia diduga disebabkan oleh cedera pada daerah inferior frontal, anterior temporal termasuk basal otak depan, juga peningkatan kerja saraf simpatis. Insomnia meningkatkan resiko stroke, disabilitas dan gangguan suasana hati. Hipersomnia setelah cedera kepala terjadi sebanyak 28%. Hipersomnia diduga akibat penurunan orexin dan akibat kerusakan pada area yang mempertahankan bangun. Hipersomnia diduga berhubungan dengan penyembuhan, waktu tersita akibat tidur dan kecelakaan akibat mengantuk. Belum ada data prevalensi gangguan ritme sirkadian setelah cedera kepala. Gangguan ini disebabkan oleh cedera pada nukleus suprakiasmatik dan sering dikaitkan dengan perburukan kondisi pasien. Insomnia dan gangguan ritme sirkadian sering dihubungkan dengan lokasi tertentu dari cedera, namun hipersomnia berhubungan dengan kadar orexin dan tidak terlalu dikaitkan terhadap area tertentu. Insomnia dan gangguan ritme sirkadian berhubungan dengan perburukan, namun hipersomnia bisa menandakan perbaikan dan tidak berhubungan signifikan dengan gangguan lainnya. Diharapkan dengan memahami gangguan tidur ini dapat meningkatkan kewaspadaan bagi para klinisi dan mendorong untuk penelitian berikutnya sehingga penanganan pasien gangguan tidur akibat cedera kepala dapat menjadi lebih baik.